2023
DOI: 10.3390/genes14020464
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Sequencing Reveals the Involvement of Sesquiterpene Biosynthesis Genes and Transcription Factors during an Early Response to Mechanical Wounding of Aquilaria sinensis

Abstract: Plants respond to wounding by reprogramming the expression of genes involved in secondary metabolism. Aquilaria trees produce many bioactive secondary metabolites in response to wounding, but the regulatory mechanism of agarwood formation in the early response to mechanical wounding has remained unclear. To gain insights into the process of transcriptome changes and to determine the regulatory networks of Aquilaria sinensis to an early response (15 days) to mechanical wounding, we collected A. sinensis samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…And a finding done by Singh et al suggested a relationship between sesquiterpenes, phenolics, flavonoids, and the antioxidant capacity of Ferula plants [48]. Moreover, a study had proposed that the synthesis of sesquiterpenes, triterpenes, flavonoids, and phenylpropanoids might play a crucial role in the response to mechanical damage in Aquilaria sinensis [49].…”
Section: Discussionmentioning
confidence: 99%
“…And a finding done by Singh et al suggested a relationship between sesquiterpenes, phenolics, flavonoids, and the antioxidant capacity of Ferula plants [48]. Moreover, a study had proposed that the synthesis of sesquiterpenes, triterpenes, flavonoids, and phenylpropanoids might play a crucial role in the response to mechanical damage in Aquilaria sinensis [49].…”
Section: Discussionmentioning
confidence: 99%
“…After assembly of the mapped reads, the unigenes were run against a non-redundant database. Differentially expressed genes (DEGs) were determined with a cutoff of |log2 fold change (MB/MP)|≥ 1 and adjusted p -value ≤ 0.05, as the criteria used in the previous study [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…RSEM (h p://deweylab.biostat.wisc.edu/rsem/) was used to quantify gene abundances [57]. DEGs were determined with a cutoff of |log2 fold change (RNAi/control) |≥ 1 and p-value ≤ 0.05, as the criteria used in the previous study [58]. In addition, functional-enrichment analysis including GO (Gene Ontology, h p://www.geneontology.org) and KEGG (Kyoto Encyclopedia of Genes and Genomes, h p://www.genome.jp/kegg/) were performed to identify which DEGs were significantly enriched in GO terms and metabolic pathways at P value≤0.05 compared with the whole-transcriptome background.…”
Section: Rna Extraction Library Preparation and Sequencingmentioning
confidence: 99%